How does Teach For America engage its alumni politically? A case study in Detroit - Singer, Jeremy; Brewer, T. Jameson (Education Policy Analysis Archives, 2021)
We describe the alumni engagement efforts by Teach For America (TFA) in Detroit as a case study of the specific ways that the organization works to influence its alumni’s involvement in educational politics and disposition towards particular types of educational reform. During the 2019-20 school year, TFA Detroit facilitated a series of “policy workshops” for its alumni, intended to inspire TFA corps members and alumni to engage in political and policy advocacy. Combining field notes and other artifacts from the policy workshops with a social network analysis of the featured participants and central organizations, we show that TFA Detroit drew upon its local, state, and national policy networks to construct workshops that in turn would politically mobilize alumni to support their networks’ preferred city and state policies and reforms.